2018
DOI: 10.1111/jpy.12779
|View full text |Cite
|
Sign up to set email alerts
|

Symbiochlorum hainanensis gen. et sp. nov. (Ulvophyceae, Chlorophyta) isolated from bleached corals living in the South China Sea

Abstract: Light/scanning electron/transmission microscopy-based morphological analyses and multiple nucleotide sequences-based molecular phylogenetic analyses are used to identify and assess the phylogenetic position of a new unidentified green alga isolated from bleached corals living in the South China Sea. This new unidentified green alga is a unicellular marine alga and has uninucleate vegetative cells and multiple chloroplasts with a pyrenoid. It can form aplanosporangium covered by cell walls and reproduces by rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 22 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Cultures of S. hainanensis (CCTCC M2018096), isolated from coral species Porites lutea in the tropical reef regions of the SCS (Gong et al, 2018(Gong et al, , 2019, were incubated in 250-ml Erlenmeyer flasks with 100 ml autoclaved artificial seawater medium (Formula grade A Reef Sea Salt, Formula, Japan) under an in situ temperature of 26 • C, light intensity of 90 µmol photon m −2 s −1 with a 12-h/12-h light/dark cycle. The cultures were shaken at least three times a day.…”
Section: Cultures and Experimental Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Cultures of S. hainanensis (CCTCC M2018096), isolated from coral species Porites lutea in the tropical reef regions of the SCS (Gong et al, 2018(Gong et al, , 2019, were incubated in 250-ml Erlenmeyer flasks with 100 ml autoclaved artificial seawater medium (Formula grade A Reef Sea Salt, Formula, Japan) under an in situ temperature of 26 • C, light intensity of 90 µmol photon m −2 s −1 with a 12-h/12-h light/dark cycle. The cultures were shaken at least three times a day.…”
Section: Cultures and Experimental Setupmentioning
confidence: 99%
“…Cells of S. hainanensis in the mid-exponential phase under different conditions (A, H, AH, and C) were determined based on scanning electron and transmission electron microscopy observations according to our previous study (Gong et al, 2018).…”
Section: Cell Growth and Morphology Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…The genus Symbiochlorium has been reported firstly by Gong et al. ( 2018 ). So far, S. hainandiae has been only reported species within genus Symbiochlorum.…”
Section: Introductionmentioning
confidence: 99%
“…This clade of the Ulvophyceae was described as order Ignatiales by Skaloud & Leliaert in Skaloud et al [ 32 ]. Gong et al [ 33 ] found, in marine habitat on bleached corals, a coccoid green alga, which exclusively reproduced by aplanospores, and described it as Symbiochlorum hainanensis . The phylogenetic analyses revealed that this species is sister to the Ignatiales.…”
Section: Introductionmentioning
confidence: 99%